ANALISIS REPRESENTASI GENDER DALAM FILM OUR TIMES (我的少女時代) : PERSPEKTIF RELASI KEKUASAAN - Ramanda Fauziah, Intan; Ayu Wulan, Diah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze gender representation and power relations in the films Our Times. It uses a qualitative method with a discourse analysis approach, based on scenes and dialogues. The Results show that the film represents gender through traditional stereotypes, where male characters are dominant and female characters are subordinate. However, the female character develops into a more independent figure as a form of resistance. Power relations are reflected in social interactions and are dynamic. In conclusion, the film not only reflects gender inequality but also shows the potential for change.